The Influence of Democratic Leadership Style and Career Development on Employee Performance Mediated by Jambi Province Regional Secretariat Organization Bureau Employee Job Satisfaction - M. Zahari; Ali Akbar; Lamhot Timbul Situmorang (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to find out and describe the description of democratic leadership style, career development, job satisfaction and employee performance at the Regional Secretariat Organization Bureau of Jambi Province as well as to find out and analyze the influence of democratic leadership style and career development on employee performance mediated by job satisfaction at the Secretariat Organization Bureau Jambi Province Region. The method used in this research is descriptive verification and quantitative methods. Based on the approach, it can be seen that the number of samples is 62 people. This research uses the Smart PLS 3.0 analysis tool. Based on the description of e-government, competency, work motivation and employee performance in the Bureau. Based on the description of the democratic leadership style, it shows that the democratic leadership style is in the quite good category. Then for fairly good career development, the description of the job satisfaction variable is in the quite satisfied category. Meanwhile, the description of employee performance variables in the category is quite high. Based on the research results, leadership style has a positive and significant effect on job satisfaction, career development has a positive and significant effect on job satisfaction, democratic leadership style has a positive and significant effect on employee performance, career development has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect. significant effect on employee performance, Democratic leadership style has a positive and significant effect on employee performance mediated by job satisfaction and career development does not have a significant effect on employee performance mediated by job satisfaction.